SUKUK ISSUANCE AND COMPANY FINANCIAL PERFORMANCE IN 2018-2022 - Nurlia Nurlia; Fitriani Fitriani; Irma Maria Dulame; Klemens Mere; Anindita Evelyn Jessica Putri (SEAN Institute, 2022)
Sukuk issuance by an entity, where sukuk as a debt instrument is a financing option for companies, has a relationship with the entity's financial performance. The goal of this research is to see if sukuk issuance has an effect on financial performance in 13 companies from various industries that issued sukuk between 2018 and 2022. The SPSS software is used in this study to perform a simple linear regression method. The issuance of sukuk has no discernible impact on the company's financial performance as measured by Return on Assets, according to the findings (ROA)